Neuroprotective and Anti-Aging Potentials of Essential Oils from Aromatic and Medicinal Plants - Ayaz, Muhammad; Sadiq, Abdul; Junaid, Muhammad; Ullah, Farhat; Subhan, Fazal; Ahmed, Jawad (Frontiers in Aging Neuroscience, 2017)
The use of essential oils (EOs) and their components is known since long in traditional medicine and aromatherapy for the management of various diseases, and is further increased in the recent times. The neuroprotective and anti-aging potentials of EOs and their possible mechanism of actions were evaluated by numerous researchers around the globe. Several clinically important EOs and their components from Nigella sativa, Acorus gramineus, Lavandula angustifolia, Eucalyptus globulus, Mentha piperita, Rosmarinus officinalis, Jasminum sambac,Piper nigrum and so many other plants are reported for neuroprotective effects. This review was aimed to summarize the current finding on EOs tested against neurodegenerative disorders like Alzheimer disease (AD) and dementia. The effects of EOs on pathological targets of AD and dementia including amyloid deposition (Aβ), neurofibrillary tangles (NFTs), cholinergic hypofunction, oxidative stress and glutametergic abnormalities were focused. Furthermore, effects of EOs on other neurological disorders including anxiety, depression, cognitive hypofunction epilepsy and convulsions were also evaluated in detail. In conclusion, EOs were effective on several pathological targets and have improved cognitive performance in animal models and human subjects. Thus, EOs can be developed as multi-potent agents against neurological disorders with better efficacy, safety and cost effectiveness.